Atherogenic Dyslipidemia Patterns And Hypertension Severity In Type 2 Diabetes Mellitus: A Systematic Review And Meta-Analysis - Alif Nurfattah Hakim; Meidanty Gasa Nugraeni (International Journal of Health Engineering and Technology, 2026)
Atherogenic dyslipidemia and hypertension frequently co-occur in Type 2 Diabetes Mellitus (T2DM), yet the precise impact of composite lipid patterns on blood pressure severity requires comprehensive evaluation. This study conducted a systematic review of six observational studies encompassing over 7.6 million individuals to quantify this relationship. The quantitative synthesis demonstrated a highly significant positive association, revealing that patients with elevated atherogenic indices such as the Atherogenic Index of Plasma (AIP) or Lipoprotein Combined Index (LCI) that exhibited a 35% greater likelihood of experiencing severe, poorly controlled hypertension compared to those with normative profiles. Ultimately, atherogenic dyslipidemia acts as a significant, independent driver of hypertension severity. To optimize cardiovascular risk reduction, clinical management protocols for diabetic hypertension must evolve beyond isolated LDL-C targets to systematically address comprehensive atherogenic lipid profiles.